Purificação, caracterização e aplicação de uma exo-poligalacturonase de penicillium janthinellum VI2R3M - Pagnonceli, Juliana (2018)
Pectinases are enzymes in increasing use in the industrial sector as in the juice, wine, food, paper and fabric industries. They can be produced by a variety of microorganisms, but the fungi have greater advantages because they adapt to the great variety of substrates, they have a fast growth and they present wide prevalence in the environment. Pectinases act on pectin, which is one of the major components of the cell wall of plants and is rich in galacturonic acid (GalA). Among pectinases, polygalacturonase (PG) degrades the pectin molecule by acting internally and randomly in the chain, releasing oligosaccharides (endo-PG), or by attacking the non-reducing end of the chain, releasing monosaccharides (exo-PG). In view of the above, the objective of this work was to investigate the production of a polygalacturonase from the fungus Penicillium janthinellum VI2R3M, which was isolated from the Atlantic Forest of the West of Paraná, and afterwards, to purify, characterize and test a possible applicability. The enzyme was produced by culturing in Khanna medium, then purified through chromatographic columns and its purity and molecular weight confirmed by electrophoresis under denaturing conditions (SDS-PAGE). Subsequently, the enzyme was biochemically characterized in terms of pH, temperature, influence of metal ions, substrate specificity, hydrolysis products, molecular weight, kinetic parameters (Km, Vmáx, Kcat) and application of juice clarification. A PG was purified after two chromatographic steps involving ion exchange columns (DEAE-Sephadex) and molecular filtration (Sephadex G100). The purity and molecular mass (102.0 kDa) of the enzyme were determined by SDS-PAGE. The enzyme showed maximum activity at pH 5.0 and temperature at 50 °C, remaining 100% stable at 50 °C for 30 minutes and 80% at pH 3.0 to 5.0 for 24 hours. The Mg2+ metal ion increased enzyme activity significantly. Kinetic parameters, that is, Km, Vmax e Kcat for pectin hydrolysis were 2.56 mg/mL, 163.1 U/mg and 277s-¹, respectively. PG is highly specific for the polygalacturonic acid substrate and generated mono-galacturonic acid, products characteristic of exo-PG action. The clarified juices of orange, apple and mango presented an increase in transmittance at 35, 45, 49%, respectively, with reduction of color in 22, 51, 55%, respectively. In this way, the exo-PG of P. janthinellum VI2R3M has interesting biochemical characteristics for application in juice industries.